The Effect of Leadership and Organizational Culture on Employee Job Satisfaction of PT Prima Tata Solusindo Jakarta - Ambarwati Meyrisafitri (Dinasti International Journal of Education Management And Social Science, 2025)
This study employed a quantitative approach to examine the impact of leadership and organizational culture on employee job satisfaction at PT Prima Tata Solusindo, involving a sample of 75 employees. The analysis demonstrates that both leadership and organizational culture exert a statistically significant influence on employee job satisfaction. The correlation analysis reveals a strong positive relationship between leadership, organizational culture, and job satisfaction. Furthermore, the simultaneous regression analysis indicates that while leadership and organizational culture jointly contribute to job satisfaction, other variables may also play a role in influencing the outcome. Hypothesis testing was conducted using t-tests and p-values to assess the significance of each independent variable. The first hypothesis (H??), which posited that leadership (X1) does not influence job satisfaction (Y), was rejected (p = 0.001 < 0.05; t = 3.762 > 1.96), indicating that leadership has a significant and positive effect on employee job satisfaction. This finding aligns with existing literature emphasizing the importance of leadership in enhancing employee morale and engagement. The second hypothesis (H??), which proposed that organizational culture (X2) does not affect job satisfaction (Y), was also rejected (p = 0.000 < 0.05; t = 7.570 > 1.96). This confirms that organizational culture significantly contributes to employee job satisfaction, reinforcing prior studies that highlight the role of a supportive and inclusive workplace culture. The third hypothesis (H??), examining the combined influence of leadership (X1) and organizational culture (X2) on job satisfaction (Y), was likewise rejected (p = 0.001 < 0.05; t = 2.985 > 1.96), indicating a statistically significant joint effect. These results suggest that the interplay between leadership and organizational culture is a key determinant of job satisfaction in the organizational context studied. In sum, the findings support the conclusion that both leadership and organizational culture, individually and collectively, have a significant and positive impact on the job satisfaction of employees at PT Prima Tata Solusindo. These insights contribute to the broader understanding of employee well-being and can inform leadership development and cultural management practices within similar organizational settings.